First report of Giardia duodenalis assemblage F in humans and dogs in southern Brazil - Silva, Ana Clécia dos Santos; Martins, Felippe Danyel Cardoso; Ladeia, Winni Alves; Kakimori, Monica Tiemi Aline; Lucas, Juliana Izidoro; Sasse, João Pedro; Martins, Thais Agostinho; Macedo, Vilma de Fátima Rodrigues de; Murad, Valter Abou; de Barros, Luiz Daniel [UNESP]; Garcia, João Luis (Elsevier, 2022)
The present study aimed to molecularly characterize Giardia duodenalis from stool samples of humans, dogs, and cats. Molecular analyses were performed on 59 samples that tested positive for G. duodenalis on coproparasitological examinations. After extraction, the samples were first tested by nested polymerase chain reaction (n-PCR) analysis of the SSU-rRNA gene, and for the samples that were positive, the β-giardin, TPI, and GDH genes were analyzed. The amplicons obtained in the n-PCR of the β-giardin gene were subjected to PCR-restriction length polymorphism (RFLP) analysis and subsequent digestion with the enzyme HaeIII to differentiate the assemblages. Seven (11.8 %), 34 (57.7 %), and 18 (30.5 %) out of 59 samples were from humans, dogs, and cats, respectively. Nested-PCR results showed that 49.2 % (29/59) of samples were positive for the SSU-rRNA gene, with 42.9 % (3/7) of humans, 55.9 % (19/34) of dogs, and 38.9 % (7/18) of catsve. Of the other genes analyzed, β-giardin was amplified most frequently, in 34.5 % (10/29) of samples, followed by GDH in 27.6 % (8/29) of samples, and TPI in 10.3 % (3/29) of samples. Only one sample from a dog showed the amplification of all genes. PCR-RFLP analysis showed assemblage F in a human, dog, and cat samples; and assemblage C and D in dog samples. This is the first description of assemblage F in humans from Brazil and the first description of assemblage F in dogs. Further studies are needed to verify the frequency with which these infections occur, and provide information that will contribute to the molecular epidemiological understanding of giardiasis.
Keywords: Giardiasis; Molecular diagnosis; One health; Zoonosis